Peningkatan Pengetahuan Pencegahan Demam Berdarah Dengue (DBD) dan Pembutan Semprot Serai Anti Nyamuk - Irawan, Bibit; Sari, Dewi Puspito; Ani, Nur (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Background: Dengue Hemorrhagic Fever (DHF) is an acute disease with clinical manifestations of bleeding that causes shock leading to death. Community Service Objectives: to increase knowledge of DHF prevention and provide skills related to making anti-mosquito citronella spray in order to suppress the spread of DHF. This community service uses two approaches: a) Community Education, by providing counseling aimed at increasing understanding and awareness related to preventing DHF transmission b) Training, by adding activities accompanied by demonstrations or examples to produce anti-mosquito citronella spray products. Results: The implementation of socialization about DHF showed that community knowledge increased by 3.2 points, the better the knowledge the community has, the better the way the community will deal with DHF. Utilization of local citronella resources as raw materials for making anti-mosquito spray is a sustainable solution to reduce the number of DHF cases while empowering the local economy. Conclusion: An integrated education and training approach can increase community awareness and skills in preventing DHF.